2010
DOI: 10.3198/jpr2009.11.0686crc
|View full text |Cite
|
Sign up to set email alerts
|

Registration of ‘TCLF‐AN‐105’ Triticale

Abstract: ‘TCLF‐AN‐105’ (Reg. No.TCL‐009–251104, México; Reg. no. CV‐31, PI 658496) intermediate triticale (× Triticosecale Wittmack) was developed by the International Maize and Wheat Improvement Center (CIMMYT), México, and reselected and released as a forage cultivar in Mexico by the Universidad Autónoma Agraria Antonio Narro (UAAAN). TCLF‐AN‐105 was selected from the progeny of the cross CT776.81//TESM01/MUSK603 produced in the Yaqui Valley, México, in 1989. CT776.81 and TESM01/MUSK603 are two parental lines (winter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
2
1
Order By: Relevance
“…These findings are supported by Mut et al (2006). Forage yield of triticale for the present study was higher than the values reported by Kara et al (2009), Lozano-del Rio et al (2010, and Kaplan et al (2015). Hay yield of triticale lines varied between 13.86-15.94 t/ha, with the lowest value in C14 and the highest value in C1, C13, and C11, respectively (Table 2).…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…These findings are supported by Mut et al (2006). Forage yield of triticale for the present study was higher than the values reported by Kara et al (2009), Lozano-del Rio et al (2010, and Kaplan et al (2015). Hay yield of triticale lines varied between 13.86-15.94 t/ha, with the lowest value in C14 and the highest value in C1, C13, and C11, respectively (Table 2).…”
Section: Discussioncontrasting
confidence: 51%
“…During the dough stage of maturity, the grain is comprised of a starchy endosperm, protein, some lipid in the germ, and fiber (Kennelly and Weinberg, 2003;Lozano-del Rio et al, 2010). Harvesting in the dough stage of maturity improves the chance of avoiding rainfall during the silage-making process.…”
Section: Introductionmentioning
confidence: 99%
“…At each harvest, samples were collected for green forage and dry matter (DM) determination following drying for 72 h at 65°C. The forage quality of AN38 and the reference cultivar TCLF‐AN‐105 (Lozano‐del Río et al, 2010) was evaluated across three cuttings at nine locations only from the 2008 to 2012 cycles and was based on composite samples from all replicates. In the evaluation for two cuts, the average growth stages (Zadoks et al, 1974) in first cutting was booting (Zadoks scale 43) and anthesis (Zadoks scale 60) in second cutting.…”
Section: Methodsmentioning
confidence: 99%